2003
DOI: 10.1002/pon.702
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer patients' support and psychological care needs: Survey from a non‐surgical oncology clinic

Abstract: While there are numerous uncertainties surrounding prostate cancer's detection and treatment, more research focusing on the psychological needs of prostate patients is required. This study investigated the support and psychological care needs of men with prostate cancer. Patients were approached during urological oncology clinics and asked to complete the: Support Care Needs Survey (SCNS), Support Care Preferences Questionnaire, EORTC QLQ-C30 (Version 3) Measure plus Prostate Module, and the Hospital Anxiety a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
201
4
11

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(231 citation statements)
references
References 66 publications
15
201
4
11
Order By: Relevance
“…20 Patients with prostate cancer report a need for support services, such as information about offered services, educational brochures, and counselling. 21 A recent evaluation of brief therapy using behavioural activation and problem-solving skills with breast cancer patients showed that following therapy, patients had significantly decreased depression and anxiety, and increased QoL. 22 Similar programs adapted for prostate cancer have yet to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…20 Patients with prostate cancer report a need for support services, such as information about offered services, educational brochures, and counselling. 21 A recent evaluation of brief therapy using behavioural activation and problem-solving skills with breast cancer patients showed that following therapy, patients had significantly decreased depression and anxiety, and increased QoL. 22 Similar programs adapted for prostate cancer have yet to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…While oncological studies increasingly include both HRQoL and needs questionnaires [4][5][6][7][8][9][10][11][12][13], few studies have compared the two approaches and these comparisons have primarily involved correlational analysis alone [4; 7; 8; 11; 12].…”
Section: A Comparison Of the Fact-g And The Supportive Care Needs Surmentioning
confidence: 99%
“…Prostate cancer patients are likely to share common concerns with other cancer sufferers [3,4], but have reported some specific unmet psychosocial needs [5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%